Sistem Informasi Geografi Untuk Pemetaan Cakupan Desa SBS (Stop Buang Air Besar Sembarangan) di Kabupaten Kepulauan Sangihe - Meityn Disye Kasaluhe; Ferdinand Gansalangi; Yana Sambeka; Agneta Sartika Lalombo (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Community-Based Total Sanitation (STBM) is the approach to change hygiene and sanitation behavior through empowerment by triggering methods. The first pillar of the Community-Based Total Sanitation program is Stop open defecation free (SBS) which is a condition when human in a community does not defecate anywhere, but in healthy latrine facilities. In Indonesia, the number of the family (KK) who still had open defecation behavior was 37.23%.  North Sulawesi was in second place with the highest number of families who still had open defecation behavior (83.78%). This research was quantitative descriptive research that used secondary data from Sangihe Health Department. Data analysis using IBM SPSS Statistics 25 and ArcMap 10.1.4 for mapping. The results showed that there were 3 sub-districts which was the area with the lowest of SBS villages (<10%), namely the sub-districts of Kendahe, Marore Island, and South Manganitu. The average achievement of the SBS Village in the Sangihe was 18.9%. The lowest access to latrines in South Manganitu was 64.3% of access. Most of the sub-districts in the Sangihe had 11-20% of SBS village coverage. For community latrine access an average of 80.5%. It is necessary to increase the number of access to latrines, especially in areas with low access to latrines, and to provide knowledge through counseling to the community on the use of healthy latrines.